5,5′-Bis-vanillin derivatives as discriminating sensors for trivalent cations - Costero, Ana M. (2015)
Several bis-vanillin derivatives containing semicarbazone moieties have been prepared and usedin discriminating trivalent cations. The prepared probes are readily obtained and they are usuallyhighly crystalline. Depending on the ligand and the studied cations, quenching, enhancement orno changes in the fluorescence spectrum were observed. Using a series of the prepared ligandsallows distinguish between Fe3+, Cr3+ and Al3+. Detection limits and selectivity in front ofdivalent cations have been evaluated.